The Social Bifurcation of Reality: Symmetrical Construction of Knowledge in Science-Trusting and Science-Distrusting Discourses - Rughiniş, Cosima; Flaherty, Michael G. (Frontiers in Sociology, 2022)
This article proposes a conceptual framework to study the social bifurcation of reality in contrastive science-trusting and science-skeptical lay worldviews, by analyzing and integrating five concepts: staging science, quantification, emotion work, time work, and boundary maintenance. Despite the epistemological asymmetry between scientifically-informed accounts and science-skeptical or denialist ones, there are symmetrical social processes at work in the construction of lay discourses. Through conceptual analysis, we synthesize an alternative to the deficit model of contrarian discourses, replacing the model of social actors as “defective scientists” with a focus on their culturally competent agency. The proposed framework is useful for observing the parallel construction of conflicting realities in interaction and their ongoing articulation through hinge objects, such as vaccines, or sanitary masks in the Covid-19 context. We illustrate the framework through a comparative approach, presenting arguments and memes from contemporary online media in two controversies, namely vaccine-trusting versus vaccine-skeptical views, and Covid-anxious versus Covid-skeptical discourses.